Pembangunan spiritual dalam agihan dana zakat asnaf fakir dan miskin / Emie Sylviana Mohd Zahid - Mohd Zahid, Emie Sylviana (Institute of Graduate Studies, UiTM, 2018)
Spiritual development is the most basic development that needs to be developed before physical development. Among the spiritual characteristics is the love of truth and reject the falsehood. The success and excellence of one's life are based on spiritual aspects. It is able to give a positive impact to produce good Muslims, obey Allah SWT and become a useful human being to society. In enhancing the development of asnaf in Malaysia, the Department of Endowments, Zakat and Hajj JAWHAR as a zakat activity co-ordination institution has set some objectives with regard to material and spiritual needs asnaf. However, there is a gap between the practices during the implementation of the zakat system in Malaysia where most of the aid provided is more to meet material requirements than spiritual. This study focuses on the aspect of spiritual development rather than the material and problem of values and attitudes among asnaf. The aim of the study is to discuss the definition of spiritual development according to the syara' and to identify and analyze spiritual development in the distribution of zakat funds…